Detection of SARS-CoV-2 RNA Using RT-qPCR in Saliva Samples and Nasopharyngeal, Lingual, and Buccal Mucosal Swabs - Sasaki, Tomoyuki; Inoue, Osamu; Ogihara, Shinji; Kubokawa, Kayo; Oishi, Saori; Shirai, Toshiaki; Iwabuchi, Keisuke; Suzuki-Inoue, Katsue (Japanese Journal of Infectious Diseases, 2022)
Coronavirus disease 2019 is diagnosed based on the detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA in nasopharyngeal swabs or saliva samples using reverse-transcription quantitative polymerase chain reaction. Nasopharyngeal swabs should be collected by medical professionals who are covered with full personal protective equipment (PPE), while saliva samples can be collected by patients themselves without any PPE. However, collecting saliva is difficult for people who are unable to follow instructions, including infants or unconscious patients. Owing to the high viscosity of saliva, special attention is required to handle saliva samples in laboratories. To solve these problems, we compared lingual and buccal mucosal swabs (oral swabs) with nasopharyngeal swabs and saliva samples. Among 13 patients who had a positive result for SARS-CoV-2 RNA in their nasopharyngeal swabs, 8 and 10 patients had a positive result for SARS-CoV-2 RNA in their saliva (concordance rate, 61.5%) and oral swabs (76.9%), respectively. Among the eight patients with a positive result for SARS-CoV-2 RNA in saliva, seven (87.5%) had SARS-CoV-2 detected in their oral swabs. We could not obtain saliva samples from four patients, but we found perfect concordance of SARS-CoV-2 positivity between the nasopharyngeal and oral swabs. Therefore, oral swabs can be used for SARS-CoV-2 RNA detection.